КООРДИНАЦІЙНІ СПОЛУКИ КОБАЛЬТУ ТА КУПРУМУ З КАФ ЛІГАНДОМ N,N'-ДИБЕНЗИЛ-N''-ТРИХЛОРАЦЕТИЛФОСФОРТРИАМІДОМ: DOI: https://doi.org/10.17721/1728-2209.2018.1(55).6 (Вісник Київського національного університету імені Тараса Шевченка. Хімія, 2019)
Сarbacylamidophosphates is a class of organic compounds having a composition -C(O)NHP(O)=. The presence of both peptide and phosphoramidic groups in the same molecule causes a wide range of inherent biological properties. On the basis of the ligand of the carbacylamide phosphorus type (CAPh ligand) N, N'-dibenzyl-N"-trichloroacetylphosphoric triamide (HL), di- and tetramer coordination compounds were synthesized: cobalt (II) Co2L4(СH3OH)2 and copper (ІI) Cu4L4(OCH3)4. The composition and structure of the synthesized compounds was studied using the methods of IR spectroscopy, thermogravimetric and X-ray diffraction analysis. The bidentate-cyclic coordination of ligands through oxygen atoms of the phosphoryl and carbonyl groups was established on the basis of Х-ray structural analysis data. In the Co2L4(СH3OH)2 complex ionic cobalt associates together forming centroscopic dimers due to the bridging function of the phosphoryl group. The coordination sphere also includes methanol molecules, which are coordinated to the metal atom and additionally linked to the oxygen atom of the carbonyl group by hydrogen bonding, which can be considered as an additional stabilizing factor in the formation of the dimeric structure. The copper compound is a Cu4L4(OCH3)4 tetramer, in which methylate ion through ϻ3-bridging coordination bind four copper atoms to a tetramer. According to the thermogravimetric data, the first mass loss for the cobalt complex is observed in the range from 80°C to 150°C and corresponds to the loss of two methanol molecules. On the TGA curve, two exothermic effects are observed at temperatures of 218°C and 269°C, which are due to the process of oxidative degradation of organic ligands. Unlike the compound of cobalt, the tetramer complex of copper contains methylate ion, therefore the complex is resistant to a temperature of 110°С; with further rise in temperature there is a destruction of the organic part of this complex. The DTA curve shows an exothermic effect at a temperature of 168°C. Residues after the destruction of the complexes correspond to polyphosphates of copper and cobalt.
Keywords: карбациламідофосфати; 3d-метали; координаційні сполуки